2000
DOI: 10.1128/jvi.74.12.5403-5411.2000
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus (HIV)-Positive Sera Obtained Shortly after Seroconversion Neutralize Autologous HIV Type 1 Isolates on Primary Macrophages but Not on Lymphocytes

Abstract: The aim of this study was to analyze the role of humoral immunity in early human immunodeficiency virus (HIV) infection. As neutralizing activities in HIV-positive sera are rarely detectable earlier than 9 to 12 months after infection using primary lymphocytes as target cells in neutralization assays, humoral immunity is generally thought not to contribute significantly to early virus control in the patients. Besides lymphocytes, cells of the monocyte/macrophage lineage are known to be important target cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
26
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 58 publications
5
26
2
Order By: Relevance
“…The two previous reports analyzing neutralization of macrophage infection have found that Fab have similar inhibitory activity than their corresponding whole IgG (15)(16). Such discrepancies between these previous results and our findings could not be attributed to degradation, dilution, or loss of material resulting from enzymatic treatment of our Fab or F(abЈ) 2 preparations as these fragments conserved their neutralizing potency when PBMC were used as HIV-target cells.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…The two previous reports analyzing neutralization of macrophage infection have found that Fab have similar inhibitory activity than their corresponding whole IgG (15)(16). Such discrepancies between these previous results and our findings could not be attributed to degradation, dilution, or loss of material resulting from enzymatic treatment of our Fab or F(abЈ) 2 preparations as these fragments conserved their neutralizing potency when PBMC were used as HIV-target cells.…”
Section: Discussioncontrasting
confidence: 57%
“…Contrary to previous reports (15)(16), when MDM are used as target cells, the neutralizing activity of the Fab or F(abЈ) 2 of polyclonal IgG was reduced to the inhibitory activity detected when PBMC are the HIV-target cells in the neutralization assay.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…These concerns are diminished when one considers that very little neutralizing activity was detected against Env-pseudotyped viruses when assayed with serum samples from recipients of a prototypic monomeric gp120 immunogen (Table 6). Differences in neutralization sensitivity between viruses made in 293T cells and PBMC might be explained by one or more factors: (i) the relative ease of neutralizing a single clone compared to a viral quasispecies, (ii) differences in the composition of proteins on the surface of the target cells used for infection (93), (iii) glycan composition and number of Env glycoprotein spikes on the virus surface, and/or (iv) factors associated with different adhesion molecules and other cellular proteins that become embedded on the virus surface after assembly and release from various cell types (32,41,90,112). Results of a multicenter comparative assay study indicated that differences in neutralization sensitivity are unrelated to the use of JC53-BL cells compared to PBMC as targets for infection, since similar results were obtained in both cases (Montefiori et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%